CESifo World Economic Survey May 2006 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2006)
World Economic Climate: World Economic Climate remains favourable - Economic Expectations: Assessments of the current economic situation improved again, economic expectations remain optimistic - Inflation: Expectations continue to weaken somewhat - Interest Rates: Rising trend expected - Currencies: Japanese yen seen as somewhat undervalued - Special Topic: World's main economic problems – an unbalanced picture, Counterfeiting and intellectual property protection
Keywords: 330